THE BODY AND THE CULTURE AS THE LOCUS OF CANCER - Sônia Ayako Tao Maruyama; Aldenan Lima Correa da Costa; Elisete Aparecida Rubira do Espírito Santo; Roseney Bellato; Wilza Rocha Pereira (Universidade Federal do Paraná, 2006)
Illness is also a socio-cultural construction and cancer is one of the most symbology-loaded illnesses. People who experience it, go through a process of liminarity where they may emerge modified, perceiving a new meaning to life. In daily health care, we perceive that this symbolic culturally-constructed dimension has been neglected. Through an anthropological view, we try to bring out the grounds in order to re-think nursing actions towards people who experience cancer, extending their perspectives beyond the biological body.